2004
DOI: 10.2108/0289-0003(2004)21[23:tcogei]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Changes of Gene Expression in Honeybee (Apis mellifera) Brains Associated with Ages

Abstract: Honeybee (Apis mellifera) worker bees (workers) are known to perform wide variety of tasks depending on their ages. The worker's brains also show the activity and behavior-dependent chemical and structural plasticity. To test if there are any changes of gene expression associated with different ages in the worker brains, we compared the gene expression patterns between the brains of newly emerged bees and old foraging workers (foragers) by macroarray analysis. The expression of genes encoding signal transducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 37 publications
(33 reference statements)
4
21
0
Order By: Relevance
“…The corresponding insect-specific genes are therefore supposedly involved in more specialized functions. A similar conclusion can be reached from the micro- and macroarray analyses of transcripts detected in adult honey bee workers performing different tasks during their adult life cycle [6,7]. …”
Section: Resultssupporting
confidence: 67%
“…The corresponding insect-specific genes are therefore supposedly involved in more specialized functions. A similar conclusion can be reached from the micro- and macroarray analyses of transcripts detected in adult honey bee workers performing different tasks during their adult life cycle [6,7]. …”
Section: Resultssupporting
confidence: 67%
“…Transcription of several genes encoding neurotransmitter transporters, ion channels, protein kinases, and phosphatases, e.g., is enhanced in the foraging bee (Tsuchimoto et al, 2004). Oxidative stress inactivates particular proteins preferentially (Sohal et al, 1990(Sohal et al, , 1995Sohal and Weindruch, 1996;Sohal, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In the latter class is foraging (for), a previously identified cGMP-dependent protein kinase whose pharmacological activation causes precocious positive phototaxis and precocious foraging (Ben-Shahar et al, 2002. Similarly, a recent macroarray study demonstrates higher expression levels for genes involved in signal transduction, ion channels, neurotransmitter transport, transcription factors, plasma membrane proteins and most cell adhesion proteins in foragers as compared with newly emerged bees, suggesting plasticity and remodeling of neurocellular properties during aging and/or behavioral development in honey bees (Tsuchimoto et al, 2004). Using an earlier nonnormalized version of the honey bee brain cDNA library later used to develop the bee EST database, Kucharski and Maleszka (2002) showed that foragers also increase the expression of genes encoding royal jelly proteins, metabolic enzymes (␣-glucosidase, aminopeptidases, glucose dehydrogenase) and a LIM domain protein that is a putative transcription regulator.…”
Section: Honey Bee Behavioral Geneticsmentioning
confidence: 93%